(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
This research aims to discuss a type of endowment, specifically the models of the Waqf University, which today serves as a paradigm for modern education and a model for social advancement. The researcher illustrates the impact of endowment on scientific research and cultural development. The university has a close – Prevention of dividing the superintendents’ tasks and functions regarding the endowment if joint supervision is assigned to them. – Justice among the children in the endowment, as in other gifts. – Division annulment due to the extinction of the class. – If the endower appoints a specific time for the entitlement of the yield, the right of the endowment beneficiaries is established upon its occurrence. – If the endower appoints a specific place for delivering the yield, otherwise it is where the custom dictates its distribution. – Legitimacy of temporal and spatial preparation in the endowment.